Energi Terbarukan dalam Perspektif Bio-Ekonomi: Analisis Terpadu Dampak Lingkungan dan Manfaat Finansial - Rahmi; Syaifuddin Yana; Ulfia; Radhiana; Putri Mauliza; Juwita (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The purpose of this article is to look into the function of renewable energy in a bioeconomic context by undertaking an integrated study of environmental and financial benefits. The methods employed include a review of relevant literature, statistics from national and international sources, and government data on the successful adoption of renewable energy in various nations. The purpose of this article is to give the findings of an analysis that demonstrate the reduction in carbon emissions and other environmental benefits of renewable energy, as well as to examine the initial investment costs and long-term savings that may be obtained with this technology. The identified analysis gaps include technical issues such as grid integration and the need for more efficient energy storage technologies, as well as financial impediments such as high investment prices and legislative uncertainties. This article's recommendations include strengthening supportive policies, such as appealing fiscal incentives and consistent laws, as well as increasing investment in technology innovation, to promote a smoother energy transition to bio-economic sustainability. This study is expected to contribute to the future development of NRE and its sustainability, as well as policymakers and future research, in order to increase the use of renewable energy as an essential component of the worldwide sustainable development plan.